Request to release payment of 17th running bill; to confirm the revised intended completion date for performance security guarantee - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to release payment of 17th running bill; to confirm the revised intended completion date for performance security guarantee for BRACU new campus project.